2020
DOI: 10.3390/cancers12113312
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic MIR143-3p Suppresses Cell Growth in Rhabdomyosarcoma Cells by Interrupting RAS Pathways Including PAX3–FOXO1

Abstract: Rhabdomyosarcoma (RMS) is a soft tissue sarcoma most frequently found in children. In RMS, there are two major subtypes, embryonal RMS (ERMS) and alveolar RMS (ARMS). ARMS has the worse prognosis of the two owing to the formation of the chimeric PAX3–FOXO1 gene. A novel therapeutic method is required for treating ARMS. In our previous study, we found that the ectopic expression of chemically modified MIR143-3p#12 (CM-MIR143#12), which is RNase-resistant and shows the highest anti-proliferation activity among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It is important to note that while an excess of RAS signaling was not tolerated in Rh28 aRMS cells, deficient RAS signaling was also detrimental. This is shown by the effect of dominant negative HRAS in the Rh28 cells, and others have also recently found that impaired RAS signaling suppresses aRMS cell and xenograft growth 59 , 60 . The changes in RAS protein expression we observed in response to ectopic expression of constitutively active RAS effectors in both Rh28 and RMS-YM cells likely reflects the homeostatic feedback loops that occur in RAS signaling 61 .…”
Section: Discussionmentioning
confidence: 81%
“…It is important to note that while an excess of RAS signaling was not tolerated in Rh28 aRMS cells, deficient RAS signaling was also detrimental. This is shown by the effect of dominant negative HRAS in the Rh28 cells, and others have also recently found that impaired RAS signaling suppresses aRMS cell and xenograft growth 59 , 60 . The changes in RAS protein expression we observed in response to ectopic expression of constitutively active RAS effectors in both Rh28 and RMS-YM cells likely reflects the homeostatic feedback loops that occur in RAS signaling 61 .…”
Section: Discussionmentioning
confidence: 81%
“…Protein samples (1–5 µg/lane) were subjected to sodium dodecylsulphate-polyacrylamide gel electrophoresis (SDS-PAGE). The proteins in the gel were transferred to 0.45-µm polyvinylidene fluoride membranes (Immobilon-P Membrane, EMD Millipore, MA, USA) 12 . The membranes were blocked with PVDF Blocking Reagent for Can Get Signal (TOYOBO, Osaka, Japan) for 1 h. Subsequently, the membranes were incubated overnight at 4 °C with primary antibodies at a 1:1000 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were then washed 3 times with PBS containing 0.1% Tween 20, incubated further with HRP-conjugated sheep anti-mouse or donkey anti-rabbit IgG antibody (Cell Signaling Technology [CST], Inc., Danvers, MA, USA) at room temperature, and then washed 3 times with PBS containing 0.1% Tween 20. The immunoblots were visualized using the Luminata Forte Western HRP substrate (EMD Millipore) 12 . Densitometry of the immunoblots was performed using Image J (version 2.0.0-rc-69/1.52p, NIH).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations